2022
DOI: 10.1186/s12886-022-02312-2
|View full text |Cite
|
Sign up to set email alerts
|

Molluscum contagiosum of the corneal limbus in an AIDS patient: a clinicopathological case report

Abstract: Background Molluscum contagiosum, a pox virus infection, is likely to occur in the eyelid skin; however, corneal involvements by molluscum lesions are extremely rare. We report a case of molluscum contagiosum arising in the corneal limbus in an untreated AIDS patient, together with anterior segment optical coherence tomography (OCT) findings and histopathology of the excised tumor. Case presentation A 46-year-old man with AIDS was referred to our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Conjunctival myxoma shows a high intense epithelial layer and uniform hyporeflective areas [14] . We have shown that ASOCT in a patient with molluscum contagiosum revealed a homogeneous hyper-reflective elevated lesion [15] , the results of which contributed to clinical diagnosis and the managements. Taken together, all characteristic ASOCT findings in various ocular surface tumors are different from those of the apocrine hidrocystomas on the conjunctiva.…”
Section: Discussionmentioning
confidence: 81%
“…Conjunctival myxoma shows a high intense epithelial layer and uniform hyporeflective areas [14] . We have shown that ASOCT in a patient with molluscum contagiosum revealed a homogeneous hyper-reflective elevated lesion [15] , the results of which contributed to clinical diagnosis and the managements. Taken together, all characteristic ASOCT findings in various ocular surface tumors are different from those of the apocrine hidrocystomas on the conjunctiva.…”
Section: Discussionmentioning
confidence: 81%